Changes in physical, chemical and functional properties of whey protein isolate (WPI) and sugar beet pectin (SBP) conjugates formed by controlled dry-heating. (August 2017) - Qi, Phoebe X.; Xiao, Yingping; Wickham, Edward D.
Abstract: A Maillard type reaction in the dry state was utilized to create conjugates between whey protein isolate (WPI) and sugar beet pectin (SBP) to achieve improved functional properties including solubility, colloidal stability and oil-in-water emulsion stability. To optimize the reaction conditions, mixtures of WPI and SBP at varying weight ratios, 3:1, 2:1 and 1:1, were heated at 60 °C, 79% RH for 72 h. Changes in the physical properties, i.e. solubility, and chemical compositions, i.e. free sulfhydryl and amine contents were assessed using chemical assays. Bradford assay results demonstrated that the protein solubility of WPI increased significantly, ∼20% by reacting with lower levels of SBP (3:1 and 2:1) whereas the total powder solubility was not affected until an equal ratio of SBP was used, and the reduction was only ∼15%. The free sulfhydryl (SH) and primary (NH2 ) and secondary amine (NH) contents of WPI were also mitigated by conjugating with SBP. The formation of the covalent conjugates between WPI and SBP was confirmed by SDS-PAGE gel electrophoresis through staining for both proteins and glycoproteins. The UV–VIS spectroscopy showed significant changes in the molecular electronic transition states of both WPI and the feruloyl moieties of SBP upon interaction and conjugation. Measurements of ζ-potential, particles size distribution and average particle size demonstrated that the WPI-SBP conjugates prepared at the weight ratio of 3:1 were most effective at stabilizing oil-in-water emulsions than other ratios used in this work. Graphical abstract: Highlights: Dry heating of WPI (60 °C 72 h) reduced total powder solubility by ∼10%. Total powder solubility was not affected when dry-heated with <25% SBP. Protein solubility of WPI was increased by ∼20% by conjugating with <25% SBP. Chemical changes in WPI are mitigated by conjugating with SBP. WPI-SBP conjugates displayed improved oil-in-water emulsion stability.